Developing evidence-based guidelines for the safety of symptomatic drugs in multiple sclerosis during pregnancy and breastfeeding: A systematic review and Delphi consensus. (March 2023) - Iyer, Priyanka; Wiles, Kate; Ismail, Azza; Nanda, Surabhi; Murray, Katy; Hughes, Stella; Ford, Helen L; Pearson, Owen R; White, Sarah; Bonham, Nicola; Hoyle, Natasha; Witts, James; et al.
Background: Multiple sclerosis (MS) is frequently diagnosed in people of reproductive age, many of whom will become pregnant following diagnosis. Although many women report an improvement in symptoms and relapses during pregnancy, symptoms such as fatigue and spasticity are commonly reported and can worsen. Prescribing medications during pregnancy and breastfeeding presents unique challenges and guidance on the use of symptomatic therapies is limited. Objectives: This paper aims to provide a consensus on the current evidence base to facilitate informed decision-making and optimise pre-conception counselling. Methods: A list of most commonly prescribed medications for symptom management in MS was created using pregnancy and MS-related READ codes in the Welsh GP Dataset, followed by a review by MS neurologists. Results: A final list of 24 medications was generated for review. Searches were performed on each medication, and evidence graded using standardised criteria. Evidence-based recommendations were developed and distributed to experts in the field and revised according to feedback using modified Delphi criteria. Conclusions: Our guidelines provide evidence-based recommendations on the safety of symptomatic therapies during pregnancy and breastfeeding for general practitioners and specialist teams working with people with MS who are hoping to embark on pregnancy or are currently pregnant. Individual risk–benefit ratios should be considered during pre-conception counselling to optimise symptom burden and minimise harm to both parent and child.